2020
DOI: 10.1371/journal.pone.0236387
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of the domestic resumption of social production and life under the COVID-19 epidemic

Abstract: Population migration and urban traffic are two important aspects of the socioeconomic system. We analyze the trends of social production and resumption of life after the coronavirus disease 2019 (COVID-19)-influenced Spring Festival in 2020 with statistics on reported cases of COVID-19 from China's National Health Commission and big data from Baidu Migration (a platform collecting population migration data). We find that (1) the distribution of COVID-19 cases throughout mainland China has a specific spatial pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 2 publications
4
28
0
Order By: Relevance
“…The analysis of sex and its dissimilarities helps to understand the dynamics of the infection and, above all, to direct the strategies for control, treatment, design, and efficacy of the vaccine, and in general health interventions 26 . The analysis by region showed that the most impacted city was BogotĂĄ, followed by the departments of AtlĂĄntico and Valle, even though the analysis included the months when the city instituted control strategies including personal care and strict confinement, which, draws attention and alarm to consider at the time of the intervention and the resumption of social production, this following what has been found in capital cities in the world, where the first findings have provided a scientific basis for local governments to make additional decisions on the resumption of work, it is recommended to focus attention mainly on densely populated cities, with the implementation of methods and strategies for the prevention of outbreaks 27 .…”
Section: Discussionmentioning
confidence: 98%
“…The analysis of sex and its dissimilarities helps to understand the dynamics of the infection and, above all, to direct the strategies for control, treatment, design, and efficacy of the vaccine, and in general health interventions 26 . The analysis by region showed that the most impacted city was BogotĂĄ, followed by the departments of AtlĂĄntico and Valle, even though the analysis included the months when the city instituted control strategies including personal care and strict confinement, which, draws attention and alarm to consider at the time of the intervention and the resumption of social production, this following what has been found in capital cities in the world, where the first findings have provided a scientific basis for local governments to make additional decisions on the resumption of work, it is recommended to focus attention mainly on densely populated cities, with the implementation of methods and strategies for the prevention of outbreaks 27 .…”
Section: Discussionmentioning
confidence: 98%
“…We differentiate these studies by their inputs: Cellphone location (Arimura, Ha, Okumura, & Asada, 2020 ; Gao, Rao, et al., 2020 ; Kang, Gao, et al., 2020 ; Kapoor et al., 2020 ; Pepe et al., 2020 ; Roy & Kar, 2020 ; Yabe et al., 2020 ; Ye et al., 2020 ). Internet and social networks: Google (Husnayain, Shim, Fuad, & Su, 2020 ; Kapoor et al., 2020 ; Nguyen et al., 2020 ; PĂĄszto & VondrĂĄkovĂĄ, 2020 ), Baidu (Cheng et al., 2020 ; Liu, Fang, et al., 2020 ; Mu, Yeh, & Zhang, 2020 ; Shen, 2020 ; Shi et al., 2020 ; Tong, Ma, & Liu, 2020 ; Xu, Wang, Dong, Shen, & Xu, 2020 ), Facebook (Coven & Gupta, 2020 ; Heo, Lim, & Bell, 2020 ; Kuchler, Russel, & Stroebel, 2020 ), Twitter geotagged tweets (Iranmanesh & Alpar Atun, 2021 ; Li, Li, et al., 2020 ; Saeed et al., 2021 ; Yang et al., 2020 ), Weibo (Peng, Wang, Liu, & Wu, 2020 ), Quingbo (Zhu, Zheng, Liu, Li, & Wang, 2020 ). Air and sea transport (Depellegrin, Bastianini, Fadini, & Menegon, 2020 ; Snyder & Parks, 2020 ; Sun, Wandelt, & Zhang, 2020 ; Valjarević et al., 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…It is thus extremely important for governments as well as academics to seek approaches and act wisely to make an appropriate balance between economic reopening and epidemic prevention, so as to minimize the adverse social and economic consequence of living with the virus. 37,38 There has been very limited research in this field. 39,40 At the same time, the dynamic systems model presented in this study can serve as an effective means of helping to test work resumption policies for countries around the world.…”
Section: Discussionmentioning
confidence: 99%